2006
DOI: 10.1097/01202412-200601000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between iatrogenic ulnar nerve injury and angular insertion of the medial pin in supracondylar humerus fractures

Abstract: The aim of this study was to assess the correlation between the occurrence of iatrogenic ulnar nerve injury and frontal and saggital angular insertion of the medial pin in type 3 pediatric supracondylar humerus fractures treated by closed reduction and percutaneous fixation using a cross-pin configuration. Radiographs of 90 children were retrospectively reviewed and two radiographic parameters were measured. The frontal humerus-pin angle was formed between the long axis of the humerus shaft and the axis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…The reported incidence of postoperative ulnar nerve palsies ranges from 0% to 12%. 3,[12][13][14][15][16][17][18] To avoid risk to the ulnar nerve, several authors have recommended lateral-only pinning. For "normal" transverse fracture, retrospective comparisons have demonstrated no difference in loss of fixation or treatment outcomes between crossed and lateral-only pinning.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of postoperative ulnar nerve palsies ranges from 0% to 12%. 3,[12][13][14][15][16][17][18] To avoid risk to the ulnar nerve, several authors have recommended lateral-only pinning. For "normal" transverse fracture, retrospective comparisons have demonstrated no difference in loss of fixation or treatment outcomes between crossed and lateral-only pinning.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 The advantage of lateral entry pin fixation is prevention of potential iatrogenic ulnar nerve injury, which may occur due to medial placement of the pin in as many as 12% of cases. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The use of cross pinning has been the standard of care for supracondylar fractures, and it involves placing one pin in the lateral side of the epicondyle and another pin in the medial side of the epicondyle. However, due to an increased risk of iatrogenic ulnar nerve damage, different surgical techniques have since been developed (Ozçelik et al, 2006). Babal et al (2010) conducted a study to determine whether the incidence of ulnar nerve injury occurred more frequently during lateral pinning or medial pinning during the cross‐pinning procedure, and concluded that 92.3% of the nerve damage was due to the pin placed medially.…”
Section: Discussionmentioning
confidence: 99%